WD40-Repeat Proteins in Plant Cell Wall Formation: Current Evidence and Research Prospects - Guerriero, Gea; Hausman, Jean-Francois; Ezcurra, Inés (Frontiers in Plant Science, 2015)
The metabolic complexity of living organisms relies on supramolecular protein structures which ensure vital processes, such as signal transduction, transcription, translation and cell wall synthesis. In eukaryotes WD40-repeat (WDR) proteins often function as molecular “hubs” mediating supramolecular interactions. WDR proteins may display a variety of interacting partners and participate in the assembly of complexes involved in distinct cellular functions. In plants, the formation of lignocellulosic biomass involves extensive synthesis of cell wall polysaccharides, a process that requires the assembly of large transmembrane enzyme complexes, intensive vesicle trafficking, interactions with the cytoskeleton, and coordinated gene expression. Because of their function as supramolecular hubs, WDR proteins could participate in each or any of these steps, although to date only few WDR proteins have been linked to the cell wall by experimental evidence. Nevertheless, several potential cell wall-related WDR proteins were recently identified using in silico approaches, such as analyses of co-expression, interactome and conserved gene neighborhood. Notably, some WDR genes are frequently genomic neighbors of genes coding for GT2-family polysaccharide synthases in eukaryotes, and this WDR-GT2 collinear microsynteny is detected in diverse taxa. In angiosperms, two WDR genes are collinear to cellulose synthase genes, CesAs, whereas in ascomycetous fungi several WDR genes are adjacent to chitin synthase genes, chs. In this Perspective we summarize and discuss experimental and in silico studies on the possible involvement of WDR proteins in plant cell wall formation. The prospects of biotechnological engineering for enhanced biomass production are discussed.